Morphological insights into tunnel valley formation and associated landforms: A case study from western Poland - Lipka, Ewelina (LA. Landform Analysis, 2025)
The genesis of tunnel valleys, key subglacial drainage features, is a subject of debate, with significant implications for understanding past ice-sheet dynamics. This study examines two neighbouring tunnel valleys along the Poznań Phase margin of the Scandinavian Ice Sheet in western Poland. Geomorphological mapping and digital terrain analysis reveal contrasting morphologies shaped by subglacial hydrological processes. Observed features, including glacial curvilineations, outwash fans, eskers, and washboard moraines, highlight interactions between episodic high-energy meltwater discharges and sustained drainage. The results support a hybrid model of formation, emphasizing the complexity of tunnel valley genesis during deglaciation.